Derivative Potential of Unofficial Anthroponyms: Lexico-Semantic Method of Name Production - Shulska, Nataliia; Kostusiak, Nataliia; Vilchynska, Tetyana; Bachynska, Halyna; Verbovetska, Oksana; Svystun, Nina; Savchyn, Tetyana (My University, 2023)
The article carries out a derivational analysis of unofficial anthroponyms of Ukrainians, in particular, residents of Western Polissia. It has been found that nickname creation is a special linguistic phenomenon, which, on the one hand, is extraordinary in the manifestation of individual methods or word-formation models, and on the other hand, consistently preserves the dialectal word-formation norm. Despite the anthroponymic instability and the open nature of nickname nomens, they still represent a partial tendency in the use of specific lexemes, demonstrate a set of polyfunctional, patronymic, matronymic, patronymic-possessive formants inherent in this type of naming. It has been established that like in nicknames, two methods of creation are productive in surnames: lexical-semantic and morphological (suffixing). Among the analyzed folk anthroponyms, lexical-semantic formations, especially adjectives, prevail, which is caused by the productivity of nicknames-characteristics according to the external and internal features of the carriers. Such word-forming phenomena in the production of proper names as transonymization, onymization, double semanticization, semanticization of composites, compound forms, word combinations, and substantivization are characterized in detail. The lexical-thematic groups (LTGs) that most often undergo anthroponymization are comprehensively analyzed: fauna and flora names, names of clothes, shoes, dishes, details of household life, family relations, locative names, agentives. It was observed that along with the transition to the class of onyms, the word changes its emotional and evaluative color: it turns from neutral to positive (less often) or negative (comparatively more often). The following groups of onyms are subjected to transonymization during the production of nicknames: personal names, surnames, names of famous persons, movie or cartoon characters, toponyms, zoonyms. Among the factage of appellative-derived nicknames, the names of the “nomina personalia” categories are more manifested, less– “nomina impersonalia”. Despite the laws of speech economy inherent in nicknames, very often an unofficial anthroponym can be formed by a phrase or a whole sentence. Such formations are more extensive and informative, because they always have several individual characteristics (name, indication of some trait, attachment to some event, family affiliation, etc.).
Keywords: anthroponyms; dialect; word formation; nickname